Correlation Between Technological Advances On Employee Performance Using A PRIORI Method (Case Study: PLN City of Binjai) - Alya Fadillah; Pardede, A M H; Ambarita, Indah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Technology is a set of tools that can be used or utilized by humans to facilitate various forms of work. Employee performance is the ability to achieve job requirements, where a work target can be completed in a timely manner or does not exceed the time limit provided so that the goal will be in accordance with company morals and ethics. This study aims to determine the correlation of technological progress on employee performance. In this study using RapidMiner as a test of 230 data on employees of PLN Binjai City. By using the Apriori algorithm method with a minimum support value of 10% and confidence of 50%, 44 association rules are obtained in the entire set and there are 2 rules in 4 itemsets. From the test results, the best rule with the highest value is obtained, namely if the data is T7, A3, F7 then SB, which means if using Ms.Word and Ms.Excel and Ms.PPT, using FSO Mobile and PLN Mobile, using Computers and Printers and Fax Machines then employee performance is Very Good with a support value of 30% and a confidence value of 96%.